Mechanistic pain profiling in young adolescents with patellofemoral pain before and after treatment: a prospective cohort study. Issue 5 (May 2020) - Holden, Sinéad; Rathleff, Michael Skovdal; Thorborg, Kristian; Holmich, Per; Graven-Nielsen, Thomas
Abstract : Abstract: Patellofemoral pain (PFP) is a common complaint among young sports active adolescents. This study evaluated the longitudinal changes in pronociceptive and antinociceptive mechanisms in young adolescents with PFP, their impact on prognosis, and responsiveness to treatment. Adolescents (N = 151, aged 10-14 years) diagnosed with PFP were compared with age-matched controls (N = 50) and subsequently tracked while participating in an intervention focussed on activity modification. They underwent quantitative sensory testing at baseline (preintervention), 4 weeks (during initial treatment), and 12 weeks (after treatment). Pressure pain thresholds (PPTs) were recorded on the knee, shin, and elbow. Temporal summation of pain (TSP) was assessed by the increase in pain intensity during 10 repeated cuff pressure pain stimulations on the leg. Conditioned pain modulation (CPM) was defined as change in cuff pain thresholds on one leg, during painful cuff conditioning on the contralateral leg. At baseline, adolescents with PFP had decreased PPTs at the knee, shin, and elbow ( P < 0.001) as well as more facilitated TSP ( P < 0.05) compared with controls. For CPM at baseline, controls displayed an increase in cuff pain thresholds during conditioning ( P < 0.05), while those with PFP did not. More facilitated baseline TSP was associated with less improvements in pain intensity during the intervention ( P < 0.01). Pressure pain thresholds increased at both follow-ups ( P < 0.001), and the increased PPTs were associated with decreases in pain intensity ( r = 0.316; P < 0.001). Overall, TSP remained facilitated at follow-ups, and there was no change in CPM. This is the first study to demonstrate a pronociceptive mechanism as a prognostic factor in young adolescents with PFP. Abstract : Supplemental Digital Content is Available in the Text.Young adolescents with patellofemoral pain demonstrate altered pronociceptive and antinociceptive mechanisms. Greater temporal summation of pain was associated with less improvements in pain during treatment.